New insight into sugarcane industry waste utilization (press mud) for cleaner biobutanol production by using c. acetobutylicum nrrl b-527 - Nimbalkar, Pranhita R.; Khedkar, Manisha A.; Gaikwad, S. G.; Chavan, Pramod V.; Bankar, Sandip B. (Applied Biochemistry and Biotechnology, 2017)
In the present study, press mud, a sugar industry waste, was explored for biobutanol production to strengthen agricultural economy. The fermentative production of biobutanol was investigated via series of steps, viz. characterization, drying, acid hydrolysis, detoxification, and fermentation. Press mud contains an adequate amount of cellulose (22.3%) and hemicellulose (21.67%) on dry basis, and hence, it can be utilized for further acetone-butanol-ethanol (ABE) production. Drying experiments were conducted in the temperature range of 60–120 °C to circumvent microbial spoilage and enhance storability of press mud. Furthermore, acidic pretreatment variables, viz. sulfuric acid concentration, solid to liquid ratio, and time, were optimized using response surface methodology. The corresponding values were found to be 1.5% (v/v), 1:5 g/mL, and 15 min, respectively. In addition, detoxification studies were also conducted using activated charcoal, which removed almost 93–97% phenolics and around 98% furans, which are toxic to microorganisms during fermentation. Finally, the batch fermentation of detoxified press mud slurry (the sample dried at 100 °C and pretreated) using Clostridium acetobutylicum NRRL B-527 resulted in a higher butanol production of 4.43 g/L with a total ABE of 6.69 g/L. © 2017 Springer Science+Business Media New York Author keywords
Keywords: Acetone; Acetone butanol ethanols; Acidic pre treatments; Agriculture; Biobutanol; cellulose; Clostridium acetobutylicum; Detoxification; Drying; Drying Fermentation; FermentationSpoilage; Fermentative production; Pre-treatment; Press mud; Press mud Pretreatment; Response surface methodology; Sugar industry; Sulfur determination